Wide-field polygon-scanning photoacoustic microscopy of oxygen saturation at 1-MHz A-line rate - Chen, Jiangbo (Photoacoustics, 2020)
We report wide-field polygon-scanning functional OR-PAM that for the first time achieves 1-MHz A-line rate of oxygen saturation in vivo. We address two technical challenges. The first is a 1-MHz dual-wavelength pulsed laser that has sufficient pulse energy and ultrafast wavelength switching. The second is a polygon-scanning imaging probe that has a fast scanning speed, a large field of view, and great sensitivity. The OR-PAM system offers a B-scan rate of 477.5 Hz in a 12-mm range and a volumetric imaging rate of ∼1 Hz over a 12 × 5 mm(2) scanning area. We image microvasculature and blood oxygen saturation in a 12 × 12 mm(2) scanning area in 5 s. Dynamic imaging of oxygen saturation in the mouse ear is demonstrated to monitor fast response to epinephrine injection. The new wide-field fast functional imaging ability broadens the biomedical application of OR-PAM.